URGENSI DAN TANTANGAN PENGAWASAN (CONTROLLING) DI LEMBAGA PENDIDIKAN - Salim, Amil; Sirozi , Muhammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Effective supervision is a key element in educational management, aimed at ensuring the learning process goes according to plan and achieves the expected goals. In the context of globalization and technological advances, educational institutions face various challenges that require an adaptive supervisory approach. This article explores the urgency and challenges of supervision in Islamic educational institutions, emphasizing the importance of supervision not only as a form of control, but also as a tool for improving the quality of education and forming student character. The research method used is qualitative with a literature study approach, which includes collecting data from various literature sources. The findings show that supervision functions to achieve educational goals, improve the quality of education, and ensure institutional accountability. However, challenges such as limited human resources and adaptation to curriculum changes are significant obstacles. Therefore, a more effective monitoring strategy is needed to improve the quality of education in Islamic educational institutions.